Marketing Politik Dalam Pilkada Serentak Tahun 2020 (Studi Pemenangan Eka-Richi Bupati dan Wakil Bupati Terpilih 2020 ÔÇô 2024 Kabuaten Tanah Datar) - Widi Santoso; Akhyar Hanif; Ulya Fitri (Politik Islam, 2022)
This journal discusses "Political Marketing in Simultaneous Regional Head Elections in 2020 (Study of Eka-Richi Regent and Elected Deputy Regent 2020 - 2024 Winning of Tanah Datar Regency)". Writing this journal has a focus on discussing political marketing used by Eka-Richi in the 2020 simultaneous regional elections in Tanah Datar Regency. The purpose of writing this journal is to explain and analyze the political marketing strategies and problems used by Eka-Richi in winning the 2020 Simultaneous Regional Head Elections in Tanah Datar Regency. The type of research that the researcher uses is a qualitative research method with descriptive analysis. The data collection technique in this research is using┬áinterview, documentation and observation techniques. The theory used in this research is the political marketing theory of push marketing, pass marketing, and pull marketing. Based on research through observation and interview guidelines that researchers used in obtaining data, researchers obtained research results that in the process of winning the election for the Eka-Richi candidate, one of them could be obtained by using a political marketing strategy that was run by the candidate and the success team who gathered to become the Friends of Ek-Friend Volunteer Team. Richi with the political branding ÔÇ£The New Era of Tanah Datar is More AdvancedÔÇØ who succeeded in winning the 2020 simultaneous elections in Tanah Datar Regency